First proof of the capability of wastewater surveillance for COVID-19 in India through detection of genetic material of SARS-CoV-2 - Kumar, Manish; Patel, Arbind Kumar; Shah, Anil V.; Raval, Janvi; Rajpara, Neha; Joshi, Madhvi; Joshi, Chaitanya G. (The Science of the total environment, 2020)
We made the first ever successful effort in India to detect the genetic material of SARS-CoV-2 viruses to understand the capability and application of wastewater-based epidemiology (WBE) surveillance in India. Sampling was carried out on 8 and 27 May 2020 at the Old Pirana Waste Water Treatment Plant (WWTP) at Ahmedabad, Gujarat that receives effluent from Civil Hospital treating COVID-19 patients. All three, i.e. ORF1ab, N and S genes of SARS-CoV-2, were found in the influent with no genes detected in effluent collected on 8 and 27 May 2020. Increase in SARS-CoV-2 genetic loading in the wastewater between 8 and 27 May 2020 samples concurred with corresponding increase in the number of active COVID-19 patients in the city. The number of gene copies was comparable to that reported in untreated wastewaters of Australia, China and Turkey and lower than that of the USA, France and Spain. However, temporal changes in SARS-CoV-2 RNA concentrations need to be substantiated further from the perspectives of daily and short-term changes of SARS-CoV-2 in wastewater through long-term monitoring. The study results SARS-CoV-2 will assist concerned authorities and policymakers to formulate and/or upgrade COVID-19 surveillance to have a more explicit picture of the pandemic curve. While infectivity of SARS-CoV-2 through the excreted viral genetic material in the aquatic environment is still being debated, the presence and detection of genes in wastewater systems makes a strong case for the environmental surveillance of the COVID-19 pandemic. [Display omitted] •First ever report of the presence of gene of SARS-CoV-2 in the wastewater in India.•CT value is explicitly indicative of the increase of COVID-19 patient in the vicinity.•All three i.e. ORF1ab, N and S genes of SARS-CoV-2 were discerned in the influents.•None of three genes were spotted in the effluent collected on 8 and 27 May 2020.•Increase in the SARS-CoV-2 genetic loading concurred with active COVID-19 patient.